Supply chain management: new competitive realities in the automotive value chain. (31st January 2007) - Belzowski, Bruce M.; Flynn, Michael S.; Edwards, Morgan; Ban, Linda; , Gregory Martin
Previous research on the automotive industry points to the difficulty manufacturers and suppliers face in managing their supply chains. Both groups report challenges in managing the numerous supply change interfaces between companies due particularly to differing inter-company relationship models. They also report significant differences between how well they perform Supply Chain Management (SCM) tasks and how important these activities are to their companies' future success. They also discuss the major risks companies face in sourcing globally, which when combined with increasing product and manufacturing complexity leads to conflicts in business and organisational goals.